Local newspaper closures and bank loan contracts - Ma, Zhiming; Stice, Derrald; Stice, Han; Zhang, Yue (Contemporary Accounting Research, 2025)
Abstract We examine changes in bank loan contracts after borrowers experience a nearby local newspaper closure. Compared to a sample of control firms, we find that the closure of a local newspaper leads to higher interest spreads for borrowers. This effect is more pronounced when there are fewer related lenders in the syndicate, when lenders have less prior lending experience in the local area, when the closed local newspapers are associated with increases in misconduct cases, and for institutional lenders who rely more heavily on others for monitoring. In addition, we observe that loan contract amendments become less frequent, while covenant strictness increases following newspaper closures. Our main findings are robust to various research design specifications and are not driven by deteriorating local economic conditions. Our findings suggest that local media still plays a significant role in the debt markets, even as society moves deeper into the internet era.